Magic bullets and golden rules: data sampling in molecular phylogenetics - Michael P. Cummings; Meyer, A. (Zoology (Jena)Zoology (Jena), 2005)
Data collection for molecular phylogenetic studies is based on samples of both genes and taxa. In an ideal world, with no limitations to resources, as many genes could be sampled as deemed necessary to address phylogenetic problems. Given limited resources in the real world, inadequate (in terms of choice of genes or number of genes) sequences or restricted taxon sampling can adversely affect the reliability or information gained in phylogenetics. Recent empirical and simulation-based studies of data sampling in molecular phylogenetics have reached differing conclusions on how to deal with these problems. Some advocated sampling more genes, others more taxa. There is certainly no 'magic bullet' that will fit all phylogenetic problems, and no specific 'golden rules' have been deduced, other than that single genes may not always contain sufficient phylogenetic information. However, several general conclusions and suggestions can be made. One suggestion is that the determination of a multiple, but moderate number (e.g., 6-10) of gene sequences might take precedence over sequencing a larger set of genes and thereby permit the sampling of more taxa for a phylogenetic study.